Genotype-dependent changes of gene expression during somatic embryogenesis in oil palm hybrids (Elaeis oleifera x E. guineensis). - SANTOS, I. R. (2018)
Na publicação: Jonny Everson Scherwinski-Pereira; Angela Mehta.